Glaucoma and cataract surgery: two roads merging into one. Issue 1 (January 2016) - Shah, Manjool; Law, Geoffrey; Ahmed, Iqbal Ike K.
Abstract : Purpose of review: To discuss the increasing utilization of cataract extraction in the management of glaucoma and to highlight advances in surgical care that can promote synergistic treatment of these comorbid conditions. Recent findings: Recent years have demonstrated significant advances in the management of glaucoma through the use of novel microinvasive glaucoma devices. Furthermore, an increased understanding of the role of cataract surgery in the treatment of various glaucomas warrants review. Nevertheless, cataract surgery in the glaucoma patient warrants specific preoperative, intraoperative, and postoperative planning to optimize visual function and quality of life while mitigating potential risk factors for adverse events. Summary: Although the challenges of performing cataract extraction on glaucoma patients exist, the potential benefit to these patients is substantial. With attention to pre- and perioperative surgical planning and intraoperative technique, as well as with awareness and potential utilization of novel devices and treatment strategies, cataract extraction offers a unique platform for anatomical and functional improvement in this increasingly common cohort of patients.